2002
DOI: 10.1063/1.1448806
|View full text |Cite
|
Sign up to set email alerts
|

Difference in coercivity between Co/Fe and Fe/Co bilayers

Abstract: A study of the deposition order and film thickness dependence on the coercivity of ferromagnetic bilayers, ʈ Co/Fe and ʈ Fe/Co, is presented ͑the sign, '' ʈ ,'' is for indicating glass or Si substrate position͒. The magnetization of the Co layer is aligned with the in-plane direction during rf sputter deposition. The thickness is controlled in the range of 3-22 nm. Since there exists a strong exchange interaction between the two ferromagnetic layers, the magnetization reversal process occurs cooperatively. ʈ F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…On the origin of such a magnetic texture, a number of experiments have been carried out and several causes have been considered: stresses induced by sample clamping 10 and lattice mismatch, 11 magnetostatic interactions due to stepped substrates, 12,13 magnetostriction phenomena at filmsubstrate interface, 14 mechanical influence, 15 patterning, 16 growing incidence angle, 17,18 structural phase transition in growing layers, 19 and external magnetic field during growth. 6 In previous works, 8,20 an in-plane uniaxial magnetic anisotropy was observed in Co/Fe multilayers grown under the same conditions, and any influence from the substrate material, the stresses induced by sample cutting, and the precipitation of metal oxides was excluded. In the present work, 5͓Co10/Fe10͔ multilayers were simultaneously deposited on two separated substrates, in order to check the eventual influence of environmental causes such as earth and dispersed magnetic fields, or small deviations from the perpendicular incidence between the electron-beam source and substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the origin of such a magnetic texture, a number of experiments have been carried out and several causes have been considered: stresses induced by sample clamping 10 and lattice mismatch, 11 magnetostatic interactions due to stepped substrates, 12,13 magnetostriction phenomena at filmsubstrate interface, 14 mechanical influence, 15 patterning, 16 growing incidence angle, 17,18 structural phase transition in growing layers, 19 and external magnetic field during growth. 6 In previous works, 8,20 an in-plane uniaxial magnetic anisotropy was observed in Co/Fe multilayers grown under the same conditions, and any influence from the substrate material, the stresses induced by sample cutting, and the precipitation of metal oxides was excluded. In the present work, 5͓Co10/Fe10͔ multilayers were simultaneously deposited on two separated substrates, in order to check the eventual influence of environmental causes such as earth and dispersed magnetic fields, or small deviations from the perpendicular incidence between the electron-beam source and substrate.…”
Section: Resultsmentioning
confidence: 99%
“…5 The nature of the constituting elements and the deposition order are also of great importance. 6 In some cases, it has been observed that multilayers, also nonepitaxially grown, can show an in-plane uniaxial magnetic anisotropy. The causes that determine such phenomena are not well understood, several hypotheses have been advanced and specific experimental approaches have been performed in order to clarify its origin.…”
Section: Introductionmentioning
confidence: 99%
“…Change in the ordering of the bilayers is also reported to influence magnetic properties. 5 Previously, a large number of studies were completed on Fe/ Co multilayer system. Dirne et al 6 showed that an interdiffused layer can be form during deposition of Fe/ Co multilayer.…”
mentioning
confidence: 99%
“…Dirne et al 6 showed that an interdiffused layer can be form during deposition of Fe/ Co multilayer. Several thickness dependent studies 5,7,8 are also available where shape and magnetocrystalline anisotropy are rigorously studied. However, we find no studies on anneal induced behavior of Fe/ Co multilayer.…”
mentioning
confidence: 99%
See 1 more Smart Citation